Life - McLure, Kirstie; Couper, Heather; Harper, Alice ([S.l.] : TLC Video [production company] ; [S.l.] : Discovery Channel Video, 1999)
Utilizing a giant telescope in Arecibo, Puerto Rico, researchers listen to the skies for a radio signal that could indicate that other life exists in the universe
Writer, Alice Harper ; editor, Leon Ferguson ; executive producer, Stuart Carter
Narrator: John Hurt
Keywords: Life on other planets; Astronomy